PM2.5 Chemical Compositions and Aerosol Optical Properties in Beijing during the Late Fall - Huanbo Wang; Xinghua Li; Guangming Shi; Junji Cao; Chengcai Li; Fumo Yang; Yongliang Ma; Kebin He (Atmosphere, 2015)
Daily PM2.5 mass concentrations and chemical compositions together with the aerosol optical properties were measured from 8–28 November 2011 in Beijing. PM2.5 mass concentration varied from 15.6–237.5 μg∙m−3 and showed a mean value of 111.2 ± 73.4 μg∙m−3. Organic matter, NH4NO3 and (NH4)2SO4 were the major constituents of PM2.5, accounting for 39.4%, 15.4%, and 14.9% of the total mass, respectively, while fine soil, chloride salt, and elemental carbon together accounted for 27.7%. Daily scattering and absorption coefficients (σsc and σap) were in the range of 31.1–667 Mm−1 and 8.24–158.0 Mm−1, with mean values of 270 ± 200 Mm−1 and 74.3 ± 43.4 Mm−1. Significant increases in σsc and σap were observed during the pollution accumulation episodes. The revised IMPROVE algorithm was applied to estimate the extinction coefficient (bext). On average, organic matter was the largest contributor, accounting for 44.6% of bext, while (NH4)2SO4, NH4NO3, elemental carbon, and fine soil accounted for 16.3% 18.0%, 18.6%, and 2.34% of bext, respectively. Nevertheless, the contributions of (NH4)2SO4 and NH4NO3 were significantly higher during the heavy pollution periods than those on clean days. Typical pollution episodes were also explored, and it has been characterized that secondary formation of inorganic compounds is more important than carbonaceous pollution for visibility impairment in Beijing.